Graphene intercalated free-standing carbon paper coated with MnO2 for anode materials of lithium ion batteries. (10th July 2020) - Park, Jae Hyun; Choi, Won Yeong; Lee, Sangmin; Kim, Taek-Soo; Lee, Jae W.
Abstract: The composite of manganese dioxide (MnO2 ) with high theoretical capacity (1230 mAh g −1 ) and carbon nanofiber paper with high electrical conductivity is attracting attention as a next-generation battery anode material. This study proposes a facile route for coating mesoporous MnO2 on the carbon fiber by low-temperature reduction of KMnO4 and intercalating graphene into the carbon paper through vacuum filtration. The MnO2 coated carbon nanofiber (MOCNF) is synthesized in the form of paper, while maintaining the flexibility and strength with graphene intercalated between MOCNF papers. The resulting paper is applied for the lithium ion battery anode without any current collector, binder and conductor. This free-standing electrode has a discharge capacity of 945 mAh g −1 at 100 mA g −1 and shows a high discharge capacity of 545 mAh g −1 at 1000 mA g −1 even after 1000 cycles. This stable cycle performance originates from the mesoporosity of MnO2 and the intercalation of graphene, which accelerates the kinetics of redox reaction and mitigates the electrochemical isolation of MnO2 from the carbon nanofibers. This paper-type material can be a next-generation battery anode with considerable flexibility and capacity. Furthermore, the facile method of MnO2 coating and graphene intercalation can be applied to the other electrode synthesis. Graphical abstract: Image 1 Highlights: Mesoporous MnO2 was coated on the carbon fiber by low-temperature reduction of KMnO4 . Graphene layers were intercalated into the electrospun carbon sheets through facile vacuum filtration. Resultant paper was used as a lithium ion battery anode without any current collector, binder and conductor. MnO2 induced high capacity, and intercalated graphene prevented electrochemical isolation of MnO2 .